HUBUNGAN DURASI KERJA PENYAPU JALAN DENGAN TERJADINYA NYERI PUNGGUNG BAWAH DI KOTA AMBON TAHUN 2021 - Filep Marfil Tarangi; Samuel Marunaya; Laura B.S. Huwae (Fakultas Kedokteran Universitas Pattimura, 2022)
Low back pain (LBP) is one of the musculoskeletal disorders that often occur in daily life. Work-related LBP can lead to lost working hours and reduced work efficiency. Street sweeper is one of the most important jobs, if the street sweeper works for an excessive duration of work, it can cause low back pain. This study aims to determine the relationship between work duration and low back pain in street sweepers in Ambon City. The benefits of this research can be used as a reference for the government to set a policy on working hours for street sweepers. This research is a quantitative analytic study that uses Cross Sectional design. Sampling was done by consecutive sampling method and using the Oswestry Disability Index (ODI) Questionnaire. The data were analyzed using the Statistical Package for the Social Science (SPSS) program. The results of this study showed that from 72 respondents, 67 respondents (93.1%) experienced low back pain in the Minimal Disability category and 5 respondents (6.9%) experienced low back pain in the Moderate Disability category. Bivariate analysis using Chi-Square test obtained p value = 0.005 (p <0.05) which means there is a significant relationship between street sweeper’s work duration and low back pain in City of Ambon in 2021.